A construção textual da opinião no artigo de divulgação científica - Farias, Adriana Alves (2022)
The theme of this thesis is the textual construction of opinion in scientific popularization articles published in the area of History, which present the reconstruction of the Marxist revolutionary and Argentine guerrilla Che Guevara, in the historical event Cuban Revolution. The present investigation is justified, as the scientific dissemination articles participate in the system of journalistic opinion genres and are responsible for the democratization of the discoveries proposed by the science of history. The democratization process implies the popularization of historical events so that they create an environment of proximity to the daily lives of its readership. The general objective is to contribute to discursive textual studies of the discourse of scientific dissemination, and for specific purposes: 1) To examine the process of textual construction of opinion in scientific dissemination articles published in journals that deal with historical themes; 2) Explain the evaluative scale present in the opinions constructed by the scientific dissemination article, in the process of popularizing scientific knowledge (derived from historical science), and disseminated as news events. The results obtained demonstrate that rhetoric and dialectics collaborate for the construction of arguments, having as a starting point the opinions found in the Social Cognition Framework (built by the Official History), use and maintenance of the same argumentative structure to project the opinion to be adopts for the presentation of the new version produced by the scientific popularization article, themed in History. Therefore, they present themselves as news facts, popularizing and popularizing the knowledge proposed by History, in a new memorial perspective